Nanomotor-hydrogel Delivery System with Enhanced Antibacterial Performance for Wound Treatment - Ren, Jiaoyu (Langmuir : the ACS journal of surfaces and colloids, 2024)
In this study, we present a novel system consisting of nanomotors and a hydrogel. Calcium carbonate nanomotors are prepared using layer-by-layer self-assembly technology with calcium carbonate nanoparticles as the core and catalase (CAT) and polydopamine (PDA) as the shell. Calcium carbonate nanomotors were loaded into a Schiff base hydrogel to synthesize the CaCO3NM-hydrogel system. A nanomotor is a device that works on the nanoscale to convert some form of energy to mechanical energy. The motion speed of the system in 5.0 mM H2O2 aqueous solution under near-infrared light (NIR) irradiation with a power density of 1.8 W/cm2 is 13.6 μm/s. The addition of CaCO3@NM further promotes gelation and improves the mechanical properties. The energy storage modulus increases to 4.0 × 103 Pa, which is 50 times higher. Schiff base hydrogels form dynamic reversible chemical bonds due to inter- and intramolecular hydrogen bonding. They also have good self-healing properties, as observed by measuring the energy storage modulus versus the loss modulus at 1 versus 10 kHz. The results show that the system significantly inhibited the growth of both Gram-positive bacteria, Staphylococcus aureus, and Gram-negative bacteria, Escherichia coli, after 48 h, with an inhibition rate of nearly 95%. These findings provide a basis for further research and potential applications of the system in wound dressings